Information System Design for Tracking Progress and Book Order Status Using the Prototyping Method - Pambudi, Arif Prio; Sastradipraja, Cecep Kurnia; Halim, K Prihartono Aksan; Fatich, El Vionna Laellyn Nurul (Program Studi Teknik Informatika Universitas Pamulang, 2023)
The progress and status tracking system is a way to increase the writer's service satisfaction to track the progress of books to be published. Unfortunately, this tracking system has not been widely used by book publishers. There are still publishers who only use messaging applications such as WhatsApp and e-mail to inform them of the book's progress. It is not effective in providing information to the author. Therefore, the information system for tracking the progress and status of this book order was designed by applying the prototyping method. This method is considered effective in providing solutions because of its superior communication between the customers and the system developer. The progress and status tracking information system provides information on the progress of book printing to the delivery of books to authors. All information is equipped with progress graphics and update date information. With the implementation of this progress and status tracking information system, the process of conveying information about the progress of book publishing will be more effective and efficient. This will increase satisfaction for the author.